1966
DOI: 10.1139/m66-105
|View full text |Cite
|
Sign up to set email alerts
|

Lipids of Candida Utilis: Changes With Growth

Abstract: Total lipids were extracted from cells of Candida utilis grown in batch, chemostat, and phased culture. Thin-layer chromatography of the extracts showed qualitative changes in the different lipid classes with growth. Gas–liquid chromatography was used to follow quantitative changes in the fatty acid constituents. Changes were found to be analogous to those previously reported for the amino acid pool, i.e., characteristic of the medium, of growth rate, and of the environment. The significance of the changes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1969
1969
1989
1989

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 5 publications
2
18
0
Order By: Relevance
“…Standard yeast suspensions made of C. albicans cells known to be in the logarithmic growth phase (yeasts harvested 6 h after inoculation into SDB) and a similar suspension of yeasts known to be in the stationary phase (harvested 18 h after inoculation into SDB) were prepared in 0.025 M DMG, pH 6.0. The potassium efflux on treatment with 25 ,ug of candicidin per ml at 20 C was followed with a potassium-sensitive electrode.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Standard yeast suspensions made of C. albicans cells known to be in the logarithmic growth phase (yeasts harvested 6 h after inoculation into SDB) and a similar suspension of yeasts known to be in the stationary phase (harvested 18 h after inoculation into SDB) were prepared in 0.025 M DMG, pH 6.0. The potassium efflux on treatment with 25 ,ug of candicidin per ml at 20 C was followed with a potassium-sensitive electrode.…”
Section: Resultsmentioning
confidence: 99%
“…The lipid composition of yeasts is very susceptible to variations in growth conditions (17). Several workers have observed changes in the lipid composition, notably in the total amount of lipid, the degree of lipid saturation, and the relative proportions of different phospholipids during growth (4,6,16,18). Total yeast lipid and degree of unsaturation are affected by deficiency of nitrogen, phosphate, or carbon source and changes in 02 tension or temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Cejkovii & Jirkh (1978) claimed that cell division in a strain of Saccharomyces cerevisiae induced an increase in sterol content, although these workers too did not separate free and esterified sterols. The present paper reports further changes in lipid composition during the cell cycle of the strain of C. utilis used by Dawson & Craig (1966). By using an automatic phasing technique for obtaining synchronously dividing cultures, large crops of organisms could be analysed.…”
Section: Introductionmentioning
confidence: 97%
“…Most of the techniques used to obtain synchronously dividing cultures produce relatively small populations of organisms and this has been an impediment to studies, such as following changes in lipid composition (Rattray et al, 1975), which require larger quantities of cell material. Dawson & Craig (1966) were the first to report on changes in lipid composition during a yeast cell cycle, when they showed that, in nitrogen-limited Candida utilis, oscillations occurred in the contents of the major fatty-acyl residues. Later, Penman & Duffus (1976) described a continuous and exponential pattern of accumulation of total ergosterol (free and esterified) and phospholipids during the cell cycle of Kluyveromyces fragilis.…”
Section: Introductionmentioning
confidence: 99%